2017
DOI: 10.1680/jgeot.15.p.211
|View full text |Cite
|
Sign up to set email alerts
|

Site characterisation for the Ballina field testing facility

Abstract: A soft soil field testing facility has been recently established near Ballina, New SouthWales, on the east coast of Australia, which is aimed at improving design and construction methods for transport infrastructure. Several sampling, laboratory and in situ testing campaigns have been performed to characterise the material properties of the soil. High-quality laboratory testing has been performed at one location through the soil profile and a range of geophysics, cone penetrometer, seismic dilatometer, shear v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In a few cases, a stress history and normalized soil engineering properties (SHANSEP) procedure was used and this may have resulted in differences in reported values (Jardine et al 2003;Bay et al 2005). In other cases, the value of at q max represents a lower bound, such as the Ballina clay site where Kelly et al (2017) showed that the NTH method more closely aligns with at constant volume ( ≈ 29.5°) whereas the peak values are much higher, averaging around 35.7°. Similar results are observed for the soft clay at Burswood (Low et al 2011).…”
Section: Triaxial Test Interpretationsmentioning
confidence: 99%
“…In a few cases, a stress history and normalized soil engineering properties (SHANSEP) procedure was used and this may have resulted in differences in reported values (Jardine et al 2003;Bay et al 2005). In other cases, the value of at q max represents a lower bound, such as the Ballina clay site where Kelly et al (2017) showed that the NTH method more closely aligns with at constant volume ( ≈ 29.5°) whereas the peak values are much higher, averaging around 35.7°. Similar results are observed for the soft clay at Burswood (Low et al 2011).…”
Section: Triaxial Test Interpretationsmentioning
confidence: 99%
“…The comprehensive laboratory and in situ measurements reported by Kelly et al (2017) and also by Pineda et al (2016) on geotechnical characteristics of Ballina soft clay in New South Wales, Australia, deserve further interpretation. The stratigraphy is uniform between reduced levels of À2 m to À10 m; therefore, this interpretation is limited to Ballina soft clay at mid-depth of À6 m. At this depth, plasticity index, I p , is near 70%; clay size fraction, CF, is near 70%; and in situ effective vertical stress is 42 kPa.…”
mentioning
confidence: 78%
“…To facilitate the discussion, the authors also refer to the interpretation of the information presented in Kelly et al (2017) and Pineda et al (2016) by academics and practitioners, to predict the behaviour of a trial embankment built on Ballina clay improved by prefabricated vertical drains. These predictions were presented in a symposium organised by the ARC Centre of Excellence for Geotechnical Science and Engineering in Newcastle (Australia) in September 2016 (CGSE, 2016).…”
Section: Authors' Replymentioning
confidence: 99%
“…The thickness of the soft estuarine clay increases from approximately 12 to 22 m from west to east. The engineering geology at the site is described in detail by Bishop (2004), Bishop & Fityus (2006) and Kelly et al (2016).…”
Section: The Australian National Field Testing Facility (Nftf)mentioning
confidence: 99%
“…At the Australian NFTF, three large scale trial embankments have been built , four large scale footing load tests conducted, numerous bore holes drilled with high quality soil samples collected and tested in a range of laboratory apparatus (Pineda et al, 2014;Pineda et al, 2016a,b) and a range of in-situ tests including cone (Kelly et al, 2016, Li et al, 2014and Li et al, 2016 One of the aims in establishing the Australian NFTF was to leave a lasting legacy to the engineering community by making the data freely available in digital form. This will ensure that this comprehensive data set can be reused by academics and practitioners from around the world and therefore maximize the impact of this publically funded research project.…”
Section: The Australian National Field Testing Facility (Nftf)mentioning
confidence: 99%